Analisa Pengukuran Kualitas Daya dan Pengaruhnya terhadap Performa Transformator Distribusi 1600 kVA Menggunakan Power Quality Analyzer Hioki PQ3198 di PT.Salim Ivomas Pratama Tbk - Ria, Novita Vadina Marta; Rizal, Royb Fathkur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Power quality is a crucial factor affecting the performance and reliability of distribution transformers in industrial power systems. Deviations such as harmonic distortion, load imbalance, voltage fluctuations, and transient disturbances can lead to increased losses, overheating, and reduced transformer insulation life. This study aims to analyze power quality measurements and their impact on the performance of a 1600 kVA distribution transformer using the Hioki PQ3198 Power Quality Analyzer at PT. Salim Ivomas Pratama Tbk. Real-time measurements were conducted on parameters including voltage (average 396-406 V), current (460-1060 A), frequency (50 Hz), power factor, and harmonic distortion (THD voltage <8%, THD current 6-8%) in a three-phase system with ABB Dyn5 specifications, ONAN cooling, and 5.9% impedance. A quantitative descriptive method with field data analysis revealed stable voltage and frequency with no significant voltage dips/swells, and voltage harmonics complying with IEEE 519 standards, although current harmonics were relatively high due to non-linear loads like inverters. The evaluation results indicate relatively good power quality, with optimal operational efficiency and low risk to equipment degradation, supported by normal transformer oil DGA analysis (TDCG 197 ppm). However, elevated current THD poses potential efficiency losses and accelerated aging, recommending harmonic filters, periodic monitoring, and load balancing to enhance distribution system reliability. This research provides insights into the relationship between power quality and transformer performance, supporting preventive maintenance in industrial installations.